In Silico Study on Anti-inflammatory Effect of Bioactive Compounds of Velvet Bean (Mucuna pruriens) Leaves Against NF-kB Activation Pathway - Fadilaturahmah, Fadilaturahmah; Rahayu, Resti; Santoso, Putra (JSFK (Jurnal Sains Farmasi & Klinis), 2022)
Activation of nuclear factor-kB (NF-Ä¸B) receptors potently enhances pro-inflammatory cytokines production thereby promoting inflammatory reactions. NF-Ä¸B receptor inhibition is one of the targets in overcoming inflammatory reactions. One of the natural ingredients that have the potential as an anti-inflammatory is velvet bean leaf extract (Mucuna pruriens L. (DC.)) which is used by the local people of West Sumatra. This study aimed to investigate the anti-inflammatory mechanism of the bioactive compounds detected in velvet bean leaf extract against NF-Ä¸B (1U36) activation pathway using an in silico approach. The phytochemical analysis of the ethanolic extract of velvet bean leaves was performed using GC-MS. Subsequently, their potential bioactivities were explored using PASS online test, preparation of ligands, receptors, and molecular docking. The results showed that the 34 compounds contained in the miang bean leaf extract had anti-inflammatory bioactivity with a probability activity value of >0.7 based on PASS online. The docking results showed that the highest binding affinity value was found in artemin (-7.5 kcal/mol) which was higher than the standard anti-inflammatory drug ketoconazole (-7.2 kcal/mol). Therefore, one of the mechanisms of miang bean leaves as an anti-inflammatory is due to the inhibitory action of artemin on the NF-kB activation pathway.Â